2019
DOI: 10.1108/mip-07-2018-0271
|View full text |Cite
|
Sign up to set email alerts
|

The gladiatorial sponsorship arena: how ambushing impacts memory

Abstract: Purpose The practice whereby a non-official sponsor brand attempts to “ambush” an official sponsor’s rights continues to threaten sporting events. A key motivator of the ensuing regulatory response is grounded in the ambiguity that ambush marketing generates, namely, by obscuring public awareness of the legitimate sponsor. However, the cognitive processes underpinning sponsorship identification have only recently been investigated empirically. The purpose of this paper is to investigate the effects of ambush a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2026
2026

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(83 reference statements)
0
2
0
1
Order By: Relevance
“…Један од њих је тзв. Маркетинг из заседе, односно Амбуш маркетинг (Piatkowska, Zysko, Goclowska 2015;Kelly, Cornwel, Singh 2019; Grady 2016). Иако од стране многобројних аутора оправдано, Амбуш маркетинг је на граници са етичким понашањем, будући да се по својим карактеристикама категоризује у нелојално понашање према конкуренцији.…”
Section: кључни извори различитости маркетинга у индустрији спортаunclassified
“…Један од њих је тзв. Маркетинг из заседе, односно Амбуш маркетинг (Piatkowska, Zysko, Goclowska 2015;Kelly, Cornwel, Singh 2019; Grady 2016). Иако од стране многобројних аутора оправдано, Амбуш маркетинг је на граници са етичким понашањем, будући да се по својим карактеристикама категоризује у нелојално понашање према конкуренцији.…”
Section: кључни извори различитости маркетинга у индустрији спортаunclassified
“…However, this has not stopped organizations to use guerrilla marketing tactics to ambush the official sponsors of events such as Nike ambushing Adidas’ sponsorship of the Olympic Games. While ambush marketing tactics lead to diminished recall of official sponsors (Kelly et al , 2019), sponsorship activation has been lauded to protect sponsors’ investments against ambush marketing. As indicated in the results of this research, sponsorship activation and event involvement impacted consumers’ attitudes toward the sponsoring brand that activated its sponsorship compared to the non-sponsoring brand.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The adoption of special laws against ambush marketing is a very useful legal support to the organizers of sports competitions. In one study [Kelly et al, 2019], which dealt with the effects of ambush advertising on the memory of sponsors, i.e. cognitive processes on which the identification of sponsors is based, it was concluded that exposure to advertising "from an ambush" has detrimental cognitive effects.…”
Section: C C Conclusion Onclusion Onclusion Onclusionmentioning
confidence: 99%